Exciton Mott Transition in Photoexcited Semiconductor Revealed in Terahertz Absorption Spectra - Yen, Le Thi Hai (VNU Journal of Science: Mathematics - Physics, 2024)
We theoretically investigated the terahertz (THz) absorption spectra in optically excited semiconductors. By applying Bardeen-Cooper-Schriffer (BCS)-like mean field approximation, we have reproduced the spectral position of component originating from the 1s to 2p intraband transition in various density regimes. We have investigated the THz absorption spectra in various density regimes, and in a range of temperatures above the critical temperature of BCS-BEC crossover. By analysing THz absorption spectra, we have shown that the exciton Mott transition can be studied.